Advances in Cell and Immune Therapies for Melanoma - Tanase Timis; Sanda Buruiana; Delia Dima; Madalina Nistor; Ximena Maria Muresan; Diana Cenariu; Adrian-Bogdan Tigu; Ciprian Tomuleasa (Biomedicines)
The incidence rate of cutaneous melanoma is on the rise worldwide, due to increased exposure to UV radiation, aging populations, and exposure to teratogen agents. However, diagnosis is more precise, and the increased number of new cases is related to the improved diagnosis tools. Despite better early diagnosis and better therapies, melanoma has remained a significant public health challenge because of its aggressive behavior and high potential for metastasis. In 2020, cutaneous melanoma constituted approximately 1.3% of all cancer deaths that occurred within the European Union, thereby highlighting the necessity for effective prevention, timely diagnosis, and sustainable treatment measures, especially as a growing number of cases occur among younger patients. Melanoma is regarded as one of the most inflamed cancers due to its high immune cell presence and strong response to immunotherapy, fueling the need for development of immune-driven innovative treatments. Approved therapies, including immune checkpoint inhibitors (e.g., anti-PD-1 and anti-CTLA-4), have notably improved survival rates in melanoma. However, the limitations of the PD-1/PD-L1 and CTLA-4 axes inhibitors, such as low response rates, treatment resistance, and toxicity, have driven the need for continued research and advancements in treatment strategies. Current clinical trials are exploring various combinations of immune checkpoint inhibitors with costimulatory receptor agonists, chemotherapy, targeted therapies, and other immunotherapies, with the goal of improving outcomes and reducing side effects for melanoma patients. Emerging approaches, including adoptive cell therapy with tumor-infiltrating lymphocytes (TILs) and oncolytic virotherapy, are showing promise. While CAR-T cell therapy has been less successful in melanoma compared to blood cancers, ongoing research is addressing challenges like the tumor microenvironment and antigen specificity. This review provides an overview of the requirement for advances in these medications, to mark a significant step forward in melanoma management, set to bring a fresh breath of hope for patients.